2007
DOI: 10.1063/1.2806029
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control of bond breaking in amino acid complexes with tailored femtosecond pulses

Abstract: Intense femtosecond laser pulses, judiciously tailored in an adaptive, optimal control feedback loop were used to break preferentially the acyl-N ("peptide") bond of Ac-Phe-NHMe that may be regarded as a dipeptide model. We show that coherent excitation of complex wave packets in the strong-field regime allows to cleave strong backbone bonds in the molecular system preferentially, while keeping other more labile bonds intact. These results show the potential of pulse shaping as a powerful complementary analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…This can be accomplished via the multiplicative fitness parameter (A– c )( c −1 -B), where values of A and B are normalized to the unshaped pulse measurement (obtained when the Dazzler performs no phase or amplitude shaping beyond compensation of its own dispersion). We have found that setting the constant c to 0.8 yields better convergence in our experimental conditions, relative to the original implementation of unity for c 27, as this enables the GA to explore a broader range of signal strengths.…”
Section: Resultsmentioning
confidence: 87%
“…This can be accomplished via the multiplicative fitness parameter (A– c )( c −1 -B), where values of A and B are normalized to the unshaped pulse measurement (obtained when the Dazzler performs no phase or amplitude shaping beyond compensation of its own dispersion). We have found that setting the constant c to 0.8 yields better convergence in our experimental conditions, relative to the original implementation of unity for c 27, as this enables the GA to explore a broader range of signal strengths.…”
Section: Resultsmentioning
confidence: 87%
“…To avoid bias towards the noise-dominated low-signal regime, we maximize a ratio A/B with the fitness parameter (A-c)(c −1 -B), where values of A and B are normalized to the unshaped pulse measurement. We have found that setting c to 0.8 yields better convergence relative to the original implementation of unity for c [13]. If both multiplicands are negative, an infinite negative fitness is given to the pulse.…”
Section: Methodsmentioning
confidence: 99%
“…Here the localized excitations resulted in the cleavage of the stronger N-C α bonds before the energy was distributed throughout the molecule. Furthermore the use of intense femtosecond near infrared laser beams with feedbackoptimized pulse shapes has revealed preferential cleavage of specific peptide bonds 19 . This type of control has potential use as a complementary tool for protein sequencing 19 .…”
Section: Introductionmentioning
confidence: 99%